Relations entre la qualité du liège, sa composition minérale et la composition minérale des feuilles du chêne-liège (Quercus suber L.) - Courtois, Michèle; Masson, Philippe (Ann. For. Sci., 1999)
Relationships between the quality of cork, its inorganic content and the inorganic content of the leaves of the cork-oak (Quercus suber L.). The aim of this work is to set up a relationship between the quality of cork, its inorganic content and the inorganic content of the leaves of the cork-oak. The mineral contents of both leaves and cork were identified for a range of elements (nitrogen, phosphorus, potassium, calcium, magnesium, iron, copper, zinc and manganese). The quality of the cork was evaluated by experts in the cork industry on the basis of visual assessment of cork stoppers resulting from each tree. A study of correlations between the cork inorganic contents and the quality of cork demonstrates that, among those measures, only the potassium content of cork is related to the cork quality. The cork quality seems to be independent of the leaf inorganic content, which is held to be an indicator of the cork-oak mineral nutrition. (© Inra/Elsevier, Paris.)
Keywords: Cork; inorganic content; leaf; Quality; Quercus Suber L

Relations entre la qualité du liège, sa composition minérale et la composition minérale des feuilles du chêne-liège (Quercus suber L.) - Courtois, Michèle; Masson, Philippe (Ann. For. Sci., 1999)
Relationships between the quality of cork, its inorganic content and the inorganic content of the leaves of the cork-oak (Quercus suber L.). The aim of this work is to set up a relationship between the quality of cork, its inorganic content and the inorganic content of the leaves of the cork-oak. The mineral contents of both leaves and cork were identified for a range of elements (nitrogen, phosphorus, potassium, calcium, magnesium, iron, copper, zinc and manganese). The quality of the cork was evaluated by experts in the cork industry on the basis of visual assessment of cork stoppers resulting from each tree. A study of correlations between the cork inorganic contents and the quality of cork demonstrates that, among those measures, only the potassium content of cork is related to the cork quality. The cork quality seems to be independent of the leaf inorganic content, which is held to be an indicator of the cork-oak mineral nutrition. (© Inra/Elsevier, Paris.)
Keywords: Cork; inorganic content; leaf; Quality; Quercus Suber L